The Effect of Tiktok Social Media on Students' Civic Disposition (A Descriptive Study of MAN 2 Banyumas) - Lintang Ayu Permatasari; Elly Hasan Sadeli; Ratna Kartikawati (UM Purwokerto Press, 2024)
This study aims to examine the extent of the effect of the social media platform TikTok on civic disposition. The research employs a descriptive analysis method with a quantitative approach. The sample consists of students from MAN 2 Banyumas (n=193). Data collection techniques include questionnaires, literature review, documentation, observation, and interviews. The study's findings reveal that TikTok significantly affects students' civic disposition, with a significance value of 0.000 (p 0.05), indicating a moderate effect size of 0.521%. This is evidenced by the research findings highlighting suboptimal student discipline, weak responsibility in task submission, and inconsistent adherence to school rules among the students.